If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 7x + 7x = 87 Combine like terms: 7x + 7x = 14x 3 + 14x = 87 Solving 3 + 14x = 87 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 14x = 87 + -3 Combine like terms: 3 + -3 = 0 0 + 14x = 87 + -3 14x = 87 + -3 Combine like terms: 87 + -3 = 84 14x = 84 Divide each side by '14'. x = 6 Simplifying x = 6
| x^2-16=13 | | a+11=-16 | | C^2+21=85 | | 4x*x+12x+5=0 | | 2+x-6x=17 | | x+y-6=15 | | 6x-2=x*13 | | 13+h=24 | | 8+5x+4x=-10 | | -3+4x-x=18 | | -6-5x=-61 | | -10+7x=11 | | a-8=6+5a/3 | | 1/24x3 | | 6x+3=8x-17-4 | | c+40=-35 | | y=4x^2+x+3 | | 4+10x=18+17x | | 38p+7p^2=-15 | | b-4=-20 | | y=x^2/2-3x+3 | | 1/9(8x-27) | | 5x+12=8x+30 | | y=-2x^2+x+4 | | x-2(-6)=10 | | 0=x^2-4x-3 | | 6x+y=5x+2 | | 9(5x-6y)= | | 6x+y=7x-2 | | -1=x^2+2x+3 | | -6-2(y)=10 | | 6x+y=7x-1 |